Efisiensi Belanja Modal Pemerintah Daerah: Studi Pada Kabupaten/Kota di Provinsi Aceh - Cut Putri Silphia Chandra; Darwanis Darwanis; Ridwan Ibrahim (AFRE (Accounting and Financial Review), 2022)
Based on District/City Regional Government Financial Reports (LKPD) in Aceh, absorption of capital expenditures is still low compared to the previously set budget. In fact, the percentage of capital expenditure is very small compared to the total regional expenditure in each region. This study aims to determine the efficiency level of capital expenditures based on Data Envelopment Analysis (DEA) and Regional Financial Efficiency Ratios (RFER) in districts/cities in Aceh Province for the 2016 until 2019. Research input variables are capital expenditures and the research output variables are local revenue, investment, and economic growth. The research population is all districts/cities in Aceh province. The analytical method used is DEA with the help of DEAP software version 2.1 and RFER according to the Ministry of Home Affairs No.690,900,327 (1996). The results show that the efficiency level of capital expenditure in districts/cities in Aceh Province for the 2016-2019 period is better using the RFER calculation than using the DEA method. This study concludes that the use of capital expenditures in districts/cities in Aceh Province is quite efficient, so it is necessary to improve the quality of regional capital expenditure management that can encourage an increase in own source income, investment, and economic growth.DOI: https://doi.org/10.26905/afr.v5i.8037